Cultural Form of Manifestation of Value Models in the Interaction of Personal Values and Social Structures - Chmil, Hanna; Korabliova, Nadiia; Zubavina, Iryna; Kupriichuk, Vasily; Kuznietsova, Inna (International Journal of Criminology and Sociology, 2022)
Value models in society are often positioned as key factors in the formation of interpersonal interaction. In this regard, the process of forming a value model should be considered based on the pattern of social interaction. In cultural studies, as in other socio-humanities, such an internal branch of knowledge as cultural axiology was also formed. In general, cultural axiology is correlated with the implementation of the value approach as a general scientific approach. However, in cultural studies, this approach has its own specifics. The use of a value-based approach in cultural studies allows highlighting the inner side of the relationship between an individual and society. The scientific novelty of the study is determined by the structural content of the formation of values and their correlation with the practical values of the development of the social system. The authors show that the main importance is achieved through the interaction between the paradigm of social development and the expectations of the population in the process of spreading state or public ideology. The paper defines that the main goal remains to determine the possibility of adapting the social value model and the global cultural paradigm. The practical significance of the study is determined by the need to adapt post-structural social development and mitigate the transformation of the paradigm of social development in crisis socio-political periods.